STUDY OF TECHNICAL AND FINANCIAL OF FISH CAPTURE BUSSINESS OF MACKEREL GILLNET IN BENGKONG VILLAGE SEAWATERS, BENGKONG SUB DISTRICT, BATAM CITY, RIAU ISLANDS PROVINCE - Panggabean, Sari Artati; Bustari, Bustari; Nofrizal, Nofrizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT The research was conducted in December 2017 in Bengkong village seawaters, Bengkong sub district, Batam city, Riau Island Province. The method used in this research is survey method. Where this study Aims of this study to determine the feasibility in the technical aspects and the financial aspects in the mackerel gillnet. Data collection directly by involved is the fishing operation beside conducled interviews with the questionnaire aid in order to get the data and information due the financial analysis. The operation of mackerel gillnet activity done in the evening. The mackerel gillnet has a 2,5 inches of mesh size with nylon multifilament yarn material. The result of this study indicate financial analysis conducted on fishing business in Bengkong Village Seawaters  declared fishing effort is feasible to be implemented. The average net income earned by fishermen is Rp 30.322.500/ year. Based on the financial qnalysis this fishing boing Payback period for 2,5 years with ROI percentage is 39,81 %, while Benefit cost ratio is 1,15. The FRR value is 39 % greater than the interest rate of 4-10 %, it can concluded that this fish capture business technically and financially feasible. Keyword: fishing technical, financial feasible, mackerel gillnet